Analyzing Green Culture's Role in Enhancing Public Awareness and Participation in Jayapura's Environmental Policy - Maria Satya Rani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the impact of green culture on public awareness and participation in environmental policies, with a specific focus on plastic bag restrictions in Jayapura, Indonesia. As environmental challenges intensify, integrating cultural elements into policy communication has become crucial for advancing sustainability. The research employs a qualitative methodology, incorporating in-depth interviews, field observations, and document analysis to evaluate how traditional values, community leadership, and cultural symbols, such as the noken, facilitate environmental engagement. The findings underscore the significance of green culture in aligning environmental practices with local traditions, thereby enhancing public acceptance of policies. However, the study also identifies persistent challenges, including weak enforcement and limited public awareness. The recommendations highlight the importance of cultural integration, youth participation, and partnerships with religious and community leaders to encourage sustainable behavioral change. Additionally, the research emphasizes the need to strengthen infrastructure and enforcement mechanisms to ensure long-term environmental success.